Extensive forest leaf area survey aiming at detection of vegetation change in subarctic-boreal zone - Kusakabe,Tomoko; Tsuzuki,Hayato; Hughes,Gary; Sweda,Tatsuo (National Institute of Polar Research, 2000)
P(論文) The warming resulting from increasing anthropogenic carbon dioxide and other greenhouse gasses is expected to be most prominent in the subarctic-boreal region of the Northern Hemisphere. With the objective of setting up a baseline to monitor possible vegetation change in this region, a continuous vegetation profile extending 600km from Edmonton, Alberta to Cluff Lake, Saskatchewan, Canada was measured using an airborne infrared laser altimeter mounted on a helicopter. Then the distribution of leaf area index over the same 600km long transect was estimated from this vegetation profile based on a series of plot surveys on the ground to correlate the vegetation profile with leaf area index via standing stock. The distribution of leaf area index not only corresponded well with biome type, but also showed characteristic change in accordance with environmental gradient within a given biome, thus confirming that airborne laser altimetry is a powerful tool for measuring and monitoring such important vegetation characteristics as standing volume, leaf area index, etc. over an extensive area. departmental bulletin paper